Level of human trafficking management competency among the municipal executives in the first district of Biliran province. - Coco, Niña Jedelyn (Tacloban City Niña Jedelyn Coco [and] Michael Montes Gabing, 2010)
This is a descriptive study of the level of human trafficking management competency of the three municipal executives in the First District of Biliran Province. The objectives of this study includes: 1.) to identify the socio-demographic profile of the municipal executives, 2.) to determine the level of human trafficking management competency among municipal executives based on their own perception, 3.) to determine the level of human trafficking management competency among municipal executives as perceived by the household heads, 4.) to identify if there is a significant difference between the municipal executives' own assessment in their own level of competence and the household heads perception regarding their municipal executives' level of competence and 5.) to determine the relationship between socio-demographic profile of the municipal executives and their level of human trafficking management competency as perceived by the household heads.
The study utilized the enumeration survey method in identifying the municipal executives and a multistage sampling in determining the number of household heads within the First District of Biliran Province. A self-administered questionnaire was used as the major instrument for data collection. In order to analyze the data statistical mean was used in order to come up with the over-all competency-scores. Eta, r-value, p-value and point-biserial were used in determining the correlation coefficients while t-test is used in ascertaining significant difference two groups.
The findings were: 1.) only previous occupation has a highly significant relationship with the level of competence as perceived by the household heads, 2.) there is no significant difference between the municipal executives' and household heads' perception on the level of competence, 3.) the municipal executives rated themselves as having a high level of competence, and 4.) household heads perceived their municipal executive as having a high level of competence slightly higher as compared to the municipal executives' perception with respect to the average scores. Based on the findings of the study, following recommendations for future researches are hereby forwarded: 1.) an explanatory study on the factors influencing the municipal executives and household heads, and 2) future studies can include other stakeholders in governance considering the different legislations of the government
Generally, municipal executives should undergo different trainings and seminars in keeping well- informed and up-to-date in managing human trafficking and a proper agency be instituted in each municipalities that will take charge on this problem.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science